Construction and Property Investigation of Serial Pillar[5]arene-Based [1]Rotaxanes - Ma, Longtao; Han, Ying; Yan, Chaoguo; Chen, Tingting; Wang, Yang; Yao, Yong (Frontiers in Chemistry, 2022)
Although the construction and application of pillar[5]arene-based [1]rotaxanes have been extensively studied, the types of stoppers for them are limited. In this work, we designed and prepared three series of pillar[5]arene-based [1]rotaxanes (P5[1]Rs) with pentanedione derivatives, azobenzene derivatives, and salicylaldehyde derivatives as the stoppers, respectively. The obtained P5[1]Rs were fully characterized by NMR (1H, 13C, and 2D), mass spectra, and single-crystal X-ray analysis. We found that the synergic C–H···π, C–H···O interactions and N–H···O, O–H···N hydrogen bonding are the key to the stability of [1]rotaxanes. This work not only enriched the diversity of pillar[n]arene family but also gave a big boost to the pillar[n]arene-based mechanically interlocked molecules